Technological progress in the reconfiguration of work in a penitentiary context for the social reintegration of women deprived of liberty - Cantero Ramírez, Margarita; Martínez Martínez, Lorena; Guzmán Díaz, José Cruz (DIXI, 2025)
Labor markets in the 21st century have diversified due to technological advancements, creating new opportunities to ensure the human right to work from a perspective of equality, inclusion, and non-discrimination. However, sociocultural prejudices persist, limiting access to employment for specific groups, such as individuals who have served a prison sentence.Based on this premise, this study aims to analyze how technological progress has influenced the reconfiguration of work within the penitentiary context, considering it a key axis for the social reintegration of incarcerated women. To achieve this, a qualitative descriptive study was conducted.The findings highlight the expansion of labor opportunities within the penitentiary environment, the use of information and communication technologies (ICT) in these processes, and the characteristics of the human right to work that have contributed to its transformation. Additionally, the study underscores the role of collaboration with social actors and institutions that have supported employment and training initiatives within a socio-legal framework. Furthermore, it examines how these initiatives are perceived and internalized by incarcerated women, particularly through the use of technological tools.Among the conclusions, the study emphasizes the relevance of continuing multidisciplinary research that recognizes the specificities of social groups to strengthen the social fabric, where interinstitutional cooperation and collective efforts converge. This is essential to understanding the transformations in specific aspects, such as labor within the penitentiary context, and its significance for individuals deprived of liberty.
Keywords: Legal Sociology; Sociology of Work; Penitentiary System; Social Reintegration